Management of Developing Community Reading Interest in Utilizing Digital Literacy in Science and Lorong Library - Syamsuni Haji Ruddah; Jumadi Jumadi; Abdul Rahman; Sitti Aisyah Abbas (Postgraduate, University of Mataram, 2023)
This study aims to examine an important issue related to branding in the context of the public sector: namely the public interest in utilizing the Lorong library policy and utilizing digital literacy in science. This study applied a mixed-method method that analyzes data from 1.500 respondents using interview techniques and questionnaire distribution in the form of a Likerts scale. The data has been collected and analyzed in two forms, namely qualitative and quantitative forms. The results of study show that Lorong library managers apply various methods to manage people's interest in reading. Among them are carrying out various activities carried out in the library and providing free WIFI. It can be concluded that gender differences in reading interest are due to opportunities and free time, so that the development of knowledge is different between men and women and this influence on the achievement or level of welfare of the people. Furthermore, the existence of the Lorong Library is very helpful to the community, especially during Covid-19 pandemic.